Influence of structure of porous polyketone microfiltration membranes on separation of water‐in‐oil emulsions. Issue 22 (31st March 2023) - Watanabe, Tomoki; Nakagawa, Keizo; Gonzales, Ralph Rolly; Kitagawa, Tooru; Matsuoka, Atsushi; Kamio, Eiji; Yoshioka, Tomohisa; Matsuyama, Hideto
Abstract: Pressure‐driven filtration is a suitable alternative to conventional methods for separation of surfactant‐stabilized water‐in‐oil (W/O) emulsions. In this work, porous polyketone (PK) membranes for W/O emulsion separation with outstanding organic solvent resistance were prepared by non‐solvent‐induced phase separation (NIPS). The porous PK membrane structures were controlled by changing the non‐solvent concentration in the coagulation bath. The water contact angle in oil increased as the methanol concentration in the coagulation bath increased because of the formation of a rougher membrane surface, implying higher under‐oil hydrophobicity. The PK membranes were able to separate several surfactant‐stabilized W/O emulsions consisting of various organic solvents, with high oil purity value (99.9%). Permeance increased with increasing methanol concentration in coagulation bath due to the increase in membrane pore size and porosity. The best performing membrane, prepared with 45 wt% methanol coagulation bath, showed over 4000 LMH/bar permeance using emulsions of different particle sizes. Furthermore, the relationship between permeance and the ratio of the PK membrane pore size to the W/O emulsion particle size suggested that the initial permeance was dependent on pore size. The PK membranes demonstrated huge potential for W/O emulsion separation because of their easily‐controlled structures, high under‐oil hydrophobicity, and high separation performance. Abstract :